![5x - 20 = 4x + 2](https://tex.z-dn.net/?f=5x%20-%2020%20%3D%204x%20%2B%202)
X= a number making both expressions equivalent since the picture shows them being equal.
![5x - 20 = 4x + 2](https://tex.z-dn.net/?f=5x%20-%2020%20%3D%204x%20%2B%202)
1st : We will move the terms.
Note: (anything moved to the other side of the equal sign will change signs)
![5x - 4x = 2 + 20](https://tex.z-dn.net/?f=5x%20-%204x%20%3D%202%20%2B%2020)
2nd : Calculate,
![1x = 22](https://tex.z-dn.net/?f=1x%20%3D%2022)
1x = x
Meaning 1x and x are the same meaning,
![x = 22](https://tex.z-dn.net/?f=x%20%3D%2022)
Now, we must calculate with x being 22...
![5 (22) - 20](https://tex.z-dn.net/?f=5%20%2822%29%20-%2020)
Solve by multiplying first then subtracting,
![110 - 20 = 90](https://tex.z-dn.net/?f=110%20-%2020%20%3D%2090)
This means 5x - 20 = 90 and if the two expressions were equivalent then 4x + 2 should also equal 90 yet let's check...
![4(22) + 2](https://tex.z-dn.net/?f=4%2822%29%20%2B%202)
Solve by multiplying first then subtracting,
![88 + 2 = 90](https://tex.z-dn.net/?f=88%20%2B%202%20%3D%2090)
![90 = 90](https://tex.z-dn.net/?f=90%20%3D%2090)
So both expressions equal 90.
Finally, let's calculate 2x + 6 with 22 as x,
![2(22) + 6](https://tex.z-dn.net/?f=2%2822%29%20%2B%206)
Solve by multiplying first then subtracting,
![44 + 6 = 50](https://tex.z-dn.net/?f=44%20%2B%206%20%3D%2050)
---------------------------------------------------------
Answer : x = 22
---------------------------------------------------------
I hope that helps you out!!
Any more questions, please just ask me!!
~ Zoey